2020
DOI: 10.1021/acs.nanolett.0c02265
|View full text |Cite
|
Sign up to set email alerts
|

Probing Interactions between Metal–Organic Frameworks and Freestanding Enzymes in a Hollow Structure

Abstract: It has been reported that the biological functions of enzymes could be altered when they are encapsulated in metal–organic frameworks (MOFs) due to the interactions between them. Herein, we probed the interactions of catalase in solid and hollow ZIF-8 microcrystals. The solid sample with confined catalase is prepared through a reported method, and the hollow sample is generated by hollowing the MOF crystals, sealing freestanding enzymes in the central cavities of hollow ZIF-8. During the hollowing process, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 42 publications
(68 reference statements)
1
79
0
Order By: Relevance
“…Based on the above evidence, we conclude that there are three factors that collectively contribute to the improved biocatalytic cascade efficiency: (i) the enzyme structure reorientation in their lower energy form which could led to more active site exposure; [23] (ii) the enhanced interfacial contact between the enzymes and ZIF‐L after TA etching results in lower diffusional limitations as compared to the more aggregated enzymes in the small micropores; [43, 44] and (iii) the significantly improved substrate diffusion in the large mesopores. A Knudsen diffusion model [45] was further employed to quantify the enhanced substrate diffusion in the newly created mesopores.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Based on the above evidence, we conclude that there are three factors that collectively contribute to the improved biocatalytic cascade efficiency: (i) the enzyme structure reorientation in their lower energy form which could led to more active site exposure; [23] (ii) the enhanced interfacial contact between the enzymes and ZIF‐L after TA etching results in lower diffusional limitations as compared to the more aggregated enzymes in the small micropores; [43, 44] and (iii) the significantly improved substrate diffusion in the large mesopores. A Knudsen diffusion model [45] was further employed to quantify the enhanced substrate diffusion in the newly created mesopores.…”
Section: Resultsmentioning
confidence: 87%
“…Consequently,c onsistent results from FTIR and solid-state NMR reveal the hierarchically porous MOF enables the enzymes to reorientate and spread in their lower surface energy form, forming stronger coordination with the MOF framework. Based on the above evidence,weconclude that there are three factors that collectively contribute to the improved biocatalytic cascade efficiency:( i) the enzyme structure reorientation in their lower energy form which could led to more active site exposure; [23] (ii)the enhanced interfacial contact between the enzymes and ZIF-L after TA etching results in lower diffusional limitations as compared to the more aggregated enzymes in the small micropores; [43,44] and (iii)the significantly improved substrate diffusion in the large mesopores.AKnudsen diffusion model [45] was further employed to quantify the enhanced substrate diffusion in the newly created mesopores.C alculations showed that the substrate diffusion rate was improved by c.a. 14 times in the optimized TA etched ZIF-L than in the pristine,u netched ZIF-L (Supplementary Note).…”
Section: Angewandte Chemiementioning
confidence: 97%
See 3 more Smart Citations